2007
DOI: 10.1007/s11010-007-9594-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microtubules in the tolerance of cardiomyocytes to cold ischemia-reperfusion

Abstract: Before transplantation, the heart graft is preserved by the use of cold storage in order to limit ischemia-reperfusion stress. However, sustained exposure to low temperature may induce myocardial ultrastructural damage, particularly microtubules (MT) disruption. Previous data suggested that tubulin-binding agents are able to attenuate cold-induced cytoskeleton alterations. Thus, the aim of the present work was to study the influence of docetaxel (DX, a tubulin-binding taxane) on the effects of deep hypothermia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Culture preparation (Devillard et al 2008) The primary cultures of neonatal rat cardiomyocytes were prepared from 2-to 4-day-old Wistar rat hearts, as previously described (Grynberg et al 1986). Briefly, cardiomyocytes were obtained from ventricular tissue by 10 dissociating steps of 10 min each at 37 C in 0.1% trypsin (Difco, Detroit, MI, USA).…”
Section: Nanoparticle and Nanohybrid Characterizationsmentioning
confidence: 99%
“…Culture preparation (Devillard et al 2008) The primary cultures of neonatal rat cardiomyocytes were prepared from 2-to 4-day-old Wistar rat hearts, as previously described (Grynberg et al 1986). Briefly, cardiomyocytes were obtained from ventricular tissue by 10 dissociating steps of 10 min each at 37 C in 0.1% trypsin (Difco, Detroit, MI, USA).…”
Section: Nanoparticle and Nanohybrid Characterizationsmentioning
confidence: 99%
“…This prevents damage or depolymerization during vitrification of the oocytes. Beside, previous studies reported that docetaxel was showed to repair the MT damage affected from freezing by induced the MTOC to reorganization of the MT network, which formed dense spindles of MT of cardiac cell within 4 and 8 h after warmed [12]. This may be a reason why docetaxel pretreatment improve the development of vitrified-warmed oocytes.…”
Section: Discussionmentioning
confidence: 94%
“…When cyclin, CDKs and MPF function abnormally, cell development cannot proceed to the next stage. Moreover, it has been reported that docetaxel at high concentrations induces the pro-apoptotic proteins Bax and Bak while it inhibits the anti-apoptotic proteins Bcl-2 and Bcl-x-long, thus leading to cell apoptosis [4,11,12,16]. It has been reported that the cryopreservation of oocytes at an ultra-low temperature (À196°C) induces the depolymerization of MT in the oocytes [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence seem to indicate that paclitaxel might be beneficial during myocardial ischaemia-reperfusion. Studies in isolated cell models demonstrated that treatment with the paclitaxel analogue, docetaxel, reduced LDH release and oxidative stress in monolayer cultures of newborn rat ventricles submitted to hypothermia and cold ischaemia-reperfusion (Devillard et al 2008). Regarding studies in whole cardiac preparations, pretreatment with 0.3-3 ÎŒM of paclitaxel was shown to improve heart rate, left ventricular developed pressure and work index in isolated rat and rabbit hearts subjected to regional ischaemia without reperfusion (Xiao et al 2010).…”
Section: Figure 1 Effects Of Paclitaxel On Microtubule Disruption Anmentioning
confidence: 99%